SISTEMA MULTIAGENTES PARA NEGOCIAÇÃO NO AMBIENTE ICS DE COMÉRCIO ELETRÔNICO - Fonseca, Luís Carlos Costa (2003)
This work is part of a major project called ICS (Intelliget Commerce System) that has as it´s main goal to develop an Intelligent Negotiation System for Eletronic Business on the B2B category wich is being developed at UFMA (Maranhão s Federal University) under the Coordination of Prof. Dr. Sofiane Labidi. In this work we will specifically see the basic architecture proposed for the system, the technologies that bases it and in a more detailed way we will see the negotiation between sofware agents beyond its applications in the proposed system. In this context, we intend, to propose and develop a system that can automatize the negotiation mechanisms - purchase and sale of products and services - making the interactions between companies faster, more sophisticated and efficient, and thus increase even more the profits of this business. Being so, we present the ICS (Intelligent Commerce Sysrtem) as an Eletronic Business System based on Mobile Software Agent s technology that follows the OMG MASIF2 of OMG standard(OMG, 2000). Three important features of ICS are emphasized: the eletronic commerce lifecycle, the user modeling and the proposed ontologies on each of the lifecycle´s phase. Thus the ICS aims to get as end item of the negotiation, the best opportunities of purchase and sale of products and services, thus providing, a decision making support system.